Taking Stock of Empowerment Evaluation: An Empirical Review - and Miller, Robin Lin; Campbell, Rebecca (American Journal of Evaluation, 2006)
Empowerment evaluation entered the evaluation lexicon in 1993. Since that time, it has attracted many adherents, as well as vocal detractors. A prominent issue in the debates on empowerment evaluation concerns the extent to which empowerment evaluation can be readily distinguished from other approaches to evaluation that share with it an emphasis on participatory and collaborative processes, capacity development, and evaluation use. A second issue concerns the extent to which empowerment evaluation actually leads to empowered outcomes for those who have participated in the evaluation process and those who are the intended beneficiaries of the social programs that were the objects of evaluation. The authors systematically examined 47 case examples of empowerment evaluation published from 1994 through June 2005. The results suggest wide variation among practitioners in adherence to empowerment evaluation principles and weak emphasis on the attainment of empowered outcomes for program beneficiaries. Implications for theory and practice are discussed.